Virtual reality therapy: the power of role-playing social skills - Soutelo, Ana Paula (2024)
Role-play (RP) is a technique for teaching communication and training interpersonal skills, known for its effective way of transmitting learning, in which simulation is one of its main distinguishing features. Social skills, moreover, are behaviors that involve the interpersonal relationship carried out in each social context. Although social skills training is consensually considered one of the most beneficial approaches to improving social functioning in individuals with mental illness, long-term motivation deficits diminish its effectiveness. Virtual reality technology effectively solves the motivation problem, providing a realistic and immersive experience that allows for role-playing of social skills. They provide presence and allow individuals to practice and enhance their social skills. The benefits of both RP and VR technology are clear, and the combination of the two has even greater potential. However, there is still a limited amount of research on the impact of VR in the practice of RP, so further investigation is crucial.